Eye drawing using gaze estimation model - Chiu, Po Chan (Faculty of Computer Science and Information Technology, 2009)
Eye movements are an informative source of a person’s intentions. The eyes are always looking at something and their movements can reveal a lot of what a person is currently playing attention to. Interaction based on eye movement constitutes a new area of human computer interaction intended for the community of able-bodied and disabled people. Many researchers have increasingly employed eye movements in eye typing for over twenty years. However, research on eye drawing techniques is still in the nascent stage. Eye drawing interaction techniques provide a different set of problems and challenges compared to existing human computer interaction techniques. The existing eye drawing interaction techniques suffer from Midas Touch problem, a usability problem of gaze-based interaction that activates unintended selections, simply because the user is looking at the interface. Besides that, some pictures that are drawn using the existing eye drawing techniques are difficult to recognize while the other drawings that are recognizable consist of unintended gap between lines.